1996
DOI: 10.1159/000284974
|View full text |Cite
|
Sign up to set email alerts
|

Affect Memory in Depression: Evidence of Better Delayed Recall of Positive than Negative Affect Words

Abstract: It is widely accepted that depressives focus on negative memories, and forget or repress positive memories (showing a mood-congruent affective tendency). Normals have an opposite positive bias in memory (‘Pollyanna tendency’). Research evidence for depressives’ negative bias in memory comes mainly from studies of retrieval of personal experiences during depression, or from studies of such retrieval during induced mood. In the present study, the hypothesis that depressives encode and remember negative emotion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
3
16
0
3
Order By: Relevance
“…Consistent with prior research, it was hypothesized that depressed patients would recognize more moodcongruent words (i.e., depression-relevant words) than controls would, although newer studies call for some caution regarding the replicability of this bias [Banos et al, 2001;Bazin et al, 1996;Calev, 1996]. As outlined above, no clear predictions can be made concerning the extent of false recognition.…”
Section: Introductionmentioning
confidence: 89%
“…Consistent with prior research, it was hypothesized that depressed patients would recognize more moodcongruent words (i.e., depression-relevant words) than controls would, although newer studies call for some caution regarding the replicability of this bias [Banos et al, 2001;Bazin et al, 1996;Calev, 1996]. As outlined above, no clear predictions can be made concerning the extent of false recognition.…”
Section: Introductionmentioning
confidence: 89%
“…La evidencia de un autoesquema marcadamente positivo en los sujetos no deprimidos se constata en numerosos estudios (Abramson y Alloy, 1981;Greenberg et al, 1988). Asimismo, la evidencia de sesgos positivos en el procesamiento de información para los sujetos no deprimidos, también se ha mostrado consistente en muchas investigaciones (Derry y Kuiper, 1981;Greenberg et al, 1988;Hedlund y Rude, 1995;Calev, 1996). Calev (1996) se refiere a este efecto como la «tendencia pollyana».…”
Section: Discussionunclassified
“…Asimismo, la evidencia de sesgos positivos en el procesamiento de información para los sujetos no deprimidos, también se ha mostrado consistente en muchas investigaciones (Derry y Kuiper, 1981;Greenberg et al, 1988;Hedlund y Rude, 1995;Calev, 1996). Calev (1996) se refiere a este efecto como la «tendencia pollyana». En definitiva, para poder profundizar en estas explicaciones, se hace imprescindible continuar la investigación con nuevos estudios controlados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In the study of the relationship between emotion and memory, past research [1][2][3][4] has shown that depressed people have a memory bias for emotional information. The main theoretical framework regarding such a bias is mood-congruent memory (MCM) [5][6][7] , which is defined as the tendency to recall information that is conceptually congruent with one's mood.…”
Section: Introductionmentioning
confidence: 99%